Public private partnership and financial implication to government: a case study from Malaysia - Che Abdul, Amir Faisal; Mhd. Sarif, Suhaimi; Nik Mat, Nik Hziman (AMH International, 2024)
The implementation of infrastructure projects through the Public Private Partnership (PPP) that involve investments from the private sector has greatly benefited the country. Apart from being an alternative to conventional public infrastructure projects, PPP is also said to be a more efficient method as the risk of project implementation is transferred to the private partner. Even with these advantages, it cannot escape criticism, especially the implementation of PPP projects which involve financial implications to the government. The main purpose of this study is to investigate the Malaysian government's experience in the implementation of PPP projects especially regarding its financial implication issue and how the Malaysian government addresses the issue. A total of 29 officers from several government agencies were interviewed. The interview transcripts were analyzed using ATLAS. Ti application. Apart from contributing a theory regarding PPP, the results of this study have provided new knowledge on PPP, especially Malaysia's experience in dealing with financial commitment issues arising from the implementation of PPP projects. Although the context of development in other countries may differ, this Malaysian experience can be used as an example for PPP practitioners in planning PPP projects elsewhere.